Freedom of manoeuvre in Nordic bilateral diplomacy - Hans Mouritzen (Danish Institute for International Studies (DIIS), 2020)
Bilateral diplomacy has become increasingly important in today's multipolar world. A number of cases are analysed in this DIIS Working Paper, where Nordic countries have been 'disciplined' in bilateral diplomacy by the emerging great powers of Russia, China, or India. Compared to the immediate aftermath of the Cold War, with US unipolarity and EU normative power, the Nordics have experienced a narrowing of their freedom of manoeuvre. It is no longer possible, without significant costs, to criticise these great powers' internal affairs or foreign policies based on allegedly universal values. In general, it is crucial for decision-makers not to overstep their state's freedom of manoeuvre. But on the other hand, they should not be too docile and desist from occasionally challenging its limits. Trial balloons or parallel action with related countries might do exactly that.
Keywords: 330; Diplomatie; Friedenssicherung; Außenpolitik; Nordeuropa